Watershed planning using goal programming approach – A case study - PAUL, J. C.; PANIGRAHI, B.; MOHANTY, R. R. (Journal of Soil and Water Conservation, 2021)
Efficient management of agricultural resources is becoming the key issue to feed the increasing population from limited resources. The basic resources of agriculture i.e. land and water should be optimally utilised to fulfil the requirement of the people. The present study utilises goal programming (GP) approach for watershed planning of Mandakini Balinala watershed No.1. The study was conducted considering six basic objectives such as maximisation of food production, fodder production, fuel wood production, net income generation from field crops, labour employment generation and runoff water augmentation along with constraints like available land, water and human resources of the watershed. The maximization in production of the watershed is very much necessary, to satisfy the requirement of the people. The maximization in production also helps to increase the net return from the watershed, thereby improving the socio-economic condition of the farmers. The present study gives a benefit-cost ratio of 1.34 and increase in benefit of 171.36%.